Development and validation of the Multimorbidity Treatment Burden Questionnaire (MTBQ) - Daisy Gaunt; Chris Salisbury; Mei-See Man; Katherine Chaplin; Polly Duncan; Mairead Murphy (BMJ Open)
Objective To develop and validate a new scale to assess treatment burden (the effort of looking after one’s health) for patients with multimorbidity.Design Mixed-methods.Setting UK primary care.Participants Content of the Multimorbidity Treatment Burden Questionnaire (MTBQ) was based on a literature review and views from a patient and public involvement group. Face validity was assessed through cognitive interviews. The scale was piloted and the final version was tested in 1546 adults with multimorbidity (mean age 71 years) who took part in the 3D Study, a cluster randomised controlled trial. For each question, we examined the proportion of missing data and the distribution of responses. Factor analysis, Cronbach’s alpha, Spearman’s rank correlations and longitudinal regression assessed dimensional structure, internal consistency reliability, construct validity and responsiveness, respectively. We assessed interpretability by grouping the global MTBQ scores into zero and tertiles (>0) and comparing participant characteristics across these categories.Results Cognitive interviews found good acceptability and content validity. Factor analysis supported a one-factor solution. Cronbach’s alpha was 0.83, indicating internal consistency reliability. The MTBQ score had a positive association with a comparator treatment burden scale (rs 0.58, P<0.0001) and with self-reported disease burden (rs 0.43, P<0.0001), and a negative association with quality of life (rs−0.36, P<0.0001) and self-rated health (rs−0.36, P<0.0001). Female participants, younger participants and participants with mental health conditions were more likely to have high treatment burden scores. Changes in MTBQ score over 9-month follow-up were associated, as expected, with changes in measures of quality of life (EuroQol five dimensions, five level questionnaire) and patient-centred care (Patient Assessment of Chronic Illness Care).Conclusion The MTBQ is a 10-item measure of treatment burden for patients with multimorbidity that has demonstrated good content validity, construct validity, reliability and responsiveness. It is a useful research tool for assessing the impact of interventions on treatment burden.Trial registration number ISRCTN06180958.